Literature Review: Using HIRADC Method Analyzing the Risk of Work Accidents in The Manufacturing Sector in Indonesia - Nafa Khusufi, Uyun; Hakim Zakkiy Fasya, Abdul; Handayani, Dwi; Wijaya, Satriya (Jurnal KESANS : Kesehatan dan Sains, 2023)
Introduction: The development of industrialization in Indonesia has a fairly high level of development. These developments can give rise to new industry challenges and problems. One of them is the risk of work accidents in the work environment. Objective: This study aims to describe the risk of work accidents based on the HIRADC method in the manufacturing sector in Indonesia.  Method: This study is a literature review. The data sources obtained come from various databases, namely Google Scholar and the Garuda Portal in the 2017-2021 period. Result and Discussion: The results of the literature review show that physical hazards that are found in various industries such as, industries such as slipping, noise, falls and chemical hazards are hazards that are often found in basic and chemical industries.  Conclusion: The conclusion of this literature review describes the process of occupational risk analysis based on OHSAS 18001:2007. There are 5 types of hazards in the manufacturing sector. The classification of risks with high or extreme risks is the top priority to be given control. The use of HIRADC based on OHSAS 18001:2007 in the manufacturing sector shows that there are conditions that are not optimally carried out.